Effectiveness of Church Revenue Management: An Analysis of Congregational Contributions in East Ambon - Yuspico Cornelis; Victor Cornelis (Jurnal Ar Ro'is Mandalika (Armada), 2026)
This study aims to analyze the effectiveness of church revenue contributions by congregations in the Klasis of East Ambon Island, Maluku Protestant Church (GPM) during 2024. The research focuses on three main types of funds: 30% fund (contribution to the Synod), 7% fund (contribution to the Klasis), and 1% fund (contribution to the Foundation), as regulated in the 43rd Session Decision of the Synod’s Working Assembly (MPL) GPM No. 5/MPL/43/2022. The study uses a descriptive qualitative approach with secondary data sourced from the Church's Revenue and Expenditure Budget (APBG) realization reports from thirty congregations in the East Ambon Klasis region. The analysis is conducted using the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing. The research findings indicate that the majority of congregations show a very high level of effectiveness. For the 30% fund, 22 congregations were classified as very effective, 2 as moderately effective, 5 as less effective, and 3 as ineffective. For the 7% fund, 25 congregations were classified as very effective, 2 as effective, 1 as moderately effective, and 2 as ineffective. Meanwhile, for the 1% fund, 24 congregations were classified as very effective, 2 as effective, 1 as moderately effective, and 2 as ineffective. These findings suggest that most congregations exhibit high financial compliance, while some, such as Benteng Karang and Naku, consistently struggle to meet contribution targets. Overall, the financial management of the church in the East Ambon Klasis is considered effective and accountable. However, continuous mentoring and evaluation are necessary for congregations with low effectiveness in order to achieve performance equity and enhance financial compliance across the GPM service area.